Prevention and handling of Covid-19: acceleration of vaccination movement in Magelang Regency - Barkah Susanto; Angger Mahanani; Herlina Hera Pradian; Atina Harin Hayuni; Melinda Puspa Dewi; Hafizh Reza Muhammad (Community Empowerment, 2022)
This program aims to help speed up the vaccination process in the Magelang Regency area in the terms of preventing and controlling the spread of the Covid-19 virus, which has been spreading in the area for the previous two years. The activities are carried out using a system that begins with directives and direct practice at the vaccination site, as well as help in delivering community services such as data input, vaccine delivery, and documenting the final results of vaccine recipients. The districts of Muntilan, Candimulyo, Mungkid, Salaman, Borobudur, Dukun, and Mertoyudan were among those that helped with the vaccine campaign. This activity is expected to aid efforts to recover and improve public health as well as the community's economic productivity